Análise da formação de valor interativo a partir dos recursos presentes nas relações cliente-arquiteto e apoiador-criador de projetos de crowdfunding - Rodrigues, Maurinice Daniela (2019)
This thesis, consisting of three articles, aimed to analyze interactive value formation (value co-creation and co-destruction) from the resources present in the relations. The analysis of value co-destruction is more recent than value co-creation, and it lacked a systematic review. Article 1 aimed to identify and analyze the value co-destruction approaches present in the literature through a systematic literature review. In article 1 it was found that the approaches of the publications on value co-destruction are identical to those previously raised in the literature on value co-creation. In this work, an analytical framework for interactive value formation and future research was also proposed. The study of different contexts is important to recognize the nature of resources, as well as their use by service systems. Articles 2 and 3 analyzed the interactive value formation from the resources found in the architect-client and supporter-creator of crowdfunding projects relationships, respectively. These articles used the Resource Theory of Social Exchange to define resource. In article 2, in addition to the resources love, status, services, information, goods and money, the resources security and autonomy were found from the in-depth interviews with architects and clients. Among the main results it is also possible to highlight the development of four propositions in article 2. In article 3, the theoretical relationship between types of crowdfunding (reward, donation, equity, debt) and characteristics of the resources exchanged (particularism vs. concreteness) was verified. It has been found that In donation crowdfunding, the resources exchanged have more particularistic and symbolic meanings; reward, more concrete and non-particularistic; debt, more particularistic and concrete; and equity, more non-particularistic and symbolic.